Implementation of Telemedicine-Based Baby Incubator Technology to Reduce Premature Infant Mortality Rates at Taman Health Center in Sidoarjo - Guruh Irianto, Bambang; Mifthahul Maghfiroh, Anita; Rahmawati, Triana; Kholiq, Abdul; Purwanti, Dwi; Faiz Nafi'u Pradana, Much; Ramandani, Rifan; Muflih Ridwan, Muhamad; Luthfiyah, Sari (Frontiers in Community Service and Empowerment, 2025)
Puskesmas in Sidoarjo Regency do not yet have facilities for monitoring LBW in real time via android either by health workers at the health centre or the patient's family. Puskesmas Taman serves communities spread across several villages with a coverage area spread across several villages. This is an obstacle for families to get access to monitor the patient's progress, because the patient is in the NICU or ICU room. Another thing is that there is no training for users in the use of telemedicine-based Baby Incubator equipment. The role of users and families of patients is very important to keep the equipment in good condition. However, operating trainings based on new technology for users have never been conducted. Efforts to solve the above problems are to carry out counselling and assistance in the use of baby incubator equipment to users including nurses, midwives and other non-health worker users, so as to increase the knowledge of officers or users which in turn will have an impact on increasing the productivity of officers or users and improving the quality of service at the health centre. The purpose of this Community Service is to increase the role and participation of Poltekkes Kemenkes Surabaya in improving the degree of public health in the Puskesmas Taman area, Sidoarjo Regency. The results of community service through the application of telemedicine-based Baby Incubator at Puskesmas Taman are increased knowledge and skills regarding telemedicine-based baby incubator equipment. This will improve health services, especially for babies who need intensive care. The implementation of this technology provides significant benefits, including increased accessibility of health services, speed of response to patient health conditions, family involvement in care, and efficient use of resources. Assistance to Puskesmas personnel and patient families in the form of training, monitoring and evaluation of the use of appropriate technology in the form of Telemedicine-based baby incubator utilization.